Vacancy-enhanced oxygen redox and structural stability of spinel Li2Mn3O7−x. Issue 83 (29th September 2022) - Yang, Lu; Liu, Zepeng; Li, Shuwei; Hu, Zhiwei; Kong, Qingyu; Shen, Xi; Liu, Qi; Zhu, He; Chen, Jin-Ming; Haw, Shu-Chih; Gao, Yurui; Yingying, Wang; et al.
Abstract : Soft-chemistry prepared spinel [Li4/7 Mn2/7 □1/7 ]8a [Li4/7 Mn10/7 ]16d [O4− x ′ ]32e (Li2 Mn3 O7− x ) with both Li–O–□ and Li–O–Li configurations exhibits oxygen redox and low-strain features during cycling. Abstract : Vacancies have been proved effective in activating the oxygen redox and stabilizing the structure of the oxide cathode materials for the Na-ion batteries, but their effect on the cathode materials of the Li-ion batteries is unclear. We herein show that they have similar effect on spinel [Li4/7 Mn2/7 □1/7 ]8a [Li4/7 Mn10/7 ]16d [O4− x ′ ]32e .